(untitled) (Global Journal of Medical Research, 2022)
The increase in the global prevalence of overweight and obesity has prompted a wide range of strategies to reduce its impact on health Research in the field of nutrition has shown great interest in the potential of functional foods as a non- 33 pharmacological alternative to prevent or counteract obesity Here we analyzed the effects 34 of Smallanthus sonchifolius yacon flour on hypoxia oxidative stress inflammation differentiation of visceral white adipose WAT tissue in HFD-fed rats We also compared these effects with Agave inulin supplementation to better characterize the prebiotic potential of these oligofructans as functional ingredients